A proposed modification to Hy's law and Edish criteria in oncology clinical trials using aggregated historical data. (9th January 2013) - Parks, Daniel; Lin, Xiwu; Painter, Jeffery L.; Cheng, Jie; Hunt, Christine M.; Spraggs, Colin F.; Nelson, Jeanenne J.; Curtis, Lloyd; Menius, J. Alan; Lee, Kwan R.
ABSTRACT: Purpose: Identifying drug‐induced liver injury is a critical task in drug development and postapproval real‐world care. Severe liver injury is identified by the liver chemistry threshold of alanine aminotransferase (ALT) >3× upper limit of normal (ULN) and bilirubin >2× ULN, termed Hy's law by the Food and Drug Administration. These thresholds require discontinuation of the causative drug and are seldom exceeded in most patient populations. However, because maintenance of therapy is critical in the treatment of advanced cancer, customized thresholds may be useful in oncology patient populations, particularly for those with baseline liver chemistries elevations. Methods: Liver chemistry data from 31 aggregated oncology clinical trials were modeled through a truncated robust multivariate outlier detection (TRMOD) method to develop the decision boundary or threshold for examining liver injury in oncology clinical trials. Results: The boundary of TRMOD identified outliers with an ALT limit 5.0× ULN and total bilirubin limit 2.7× ULN. In addition, TRMOD was applied to the aggregated oncology data to examine fold‐baseline ALT and total bilirubin, revealing limits of ALT 6.9× baseline and bilirubin 6.5× baseline. Similar ALT and bilirubin threshold limits were observed for oncology patients both with and without liver metastases. Conclusions: These higher liver chemistry thresholds examining fold‐ULN and fold‐baseline data may be valuable in identifying potential severe liver injury and detecting liver safety signals of clinical concern in oncology clinical trials and postapproval settings while helping to avoid premature discontinuation of curative therapy. Copyright © 2013 John Wiley & Sons, Ltd.